(untitled) (Research, Society and Development, 2022)
Step by step, the technologies provided by Industry 4.0 are being inserted in the mining processes and one of the opportunities to be explored is the use of Big Data and Advanced Analytics tools. In iron ore beneficiation plants, in the milling processes, the potential gains from machine learning tools tend to be amplified when combined with mathematical models derived from process knowledge, whether empirical or phenomenological. This article presents the application of artificial neural networks for the prediction of the main product quality parameter of a milling plant, combined with empirical equations that describe the milling process, to establish whether such equations can contribute to a better performance of the predictive models.